Are the Hessdalen Lights a Reality, an Illusion, or a Mix of the Two ? - Pascoli, Gianni (Journal of Scientific Exploration, 2021)
The Hessdalen lights (HLs in the following) are luminous, floating, more or less spherical atmospheric phenomena, with a lifetime of a few seconds to sometimes several minutes. These phenomena are seen in the Hessdalen Valley in Norway for decades. Unfortunately a full understanding of these baffling events is still lacking in spite of solid working scientific projects intended to explain them. This paper tries to improve the situation. It raises the questions where the energy for the creation of the HLs comes from, and what was its nature : (geo) chemical, electric or still other ? We propose a new scenario for the Hessdalen lights. It exploits the recent idea of stable and traversable wormholes whose the potential existence is beginning to be recognized in physics. Even though appearing highly speculative, this hypothesis has not been so far explored elsewhere while it could supply a full description of the wholeness of the phenomenon. On the other side even if the probability that a HL could indeed be a wormhole is may be low, this question should not dismissed out of hand. These theoretical considerations could help to increase knowledge and understanding of both the HLs and the wormholes, drawing mutual enrichment. In other words HLs could betray the presence of hidden wormholes and we must not let slip through our fingers this possibility even if it is very tiny. In this framework we discuss of the stability, the energetics and the oversized dimension of the HLs. In physics the final arbiter is not the theory but the experiment. Thus some “simple” experiments are eventually suggested (high time resolution photometry and magnetic field measurements). Eventually, if the process described is real and after mastering it, there is a free and inexhaustible source of energy that would be derived, a tremendous breakthrough after which we could forget the controlled nuclear fusion. Regarding its structure, the paper is divided in four paragraphs 1, 2,3, 4 independent of each other. Illustrative pictures help to understand the text.